The Ranch - Steel, Danielle (London Corgi Books, 1997)
Three women who were inseparable during their college years meet again after 20 years at a ranch in Wyoming to find courage, healing and truth as they reach out to one another and rekindle old relationships.
"A journal of the land and the home in the New West."--Publisher's statement.
Keywords: Agriculture; Livestock